Exploring the molecular mechanisms of tirzepatide in alleviating metabolic dysfunction-associated fatty liver in mice through integration of metabolomics, lipidomics, and proteomics - Jinliang Liang; Huanyi Liu; Guo Lv; Xiaotong Chen; Zhaoshou Yang; Kunhua Hu; Hongyan Sun (Lipids in Health and Disease)
Abstract Clinical studies have suggested that tirzepatide may also possess hepatoprotective effects; however, the molecular mechanisms underlying this association remain unclear. In our study, we performed biochemical analyses of serum and histopathological examinations of liver tissue in mice. To preliminarily explore the molecular mechanisms of tirzepatide on metabolic dysfunction-associated fatty liver disease (MAFLD), liquid chromatography-mass spectrometry (LC-MS) was employed for comprehensive metabolomic, lipidomic, and proteomic analyses in MAFLD mice fed a high-fat diet (HFD). The results demonstrated that tirzepatide significantly reduced serum levels of alanine transaminase (ALT) and aspartate transaminase (AST), as well as hepatic triglycerides (TG) and total cholesterol (TC), indicating its efficacy in treating MAFLD. Further findings revealed that tirzepatide reduced fatty acid uptake by downregulating Cd36 and Fabp2/4, as well as enhance the mitochondrial-lysosomal function by upregulating Lamp1/2. In addition, tirzepatide promoted cholesterol efflux and reduced cholesterol reabsorption by upregulating the expression of Hnf4a, Abcg5, and Abcg8. These results suggest that tirzepatide exerts its therapeutic effects on MAFLD by reducing fatty acid uptake, promoting cholesterol excretion, and enhancing mitochondrial-lysosomal function, providing a theoretical basis for a comprehensive understanding of tirzepatide.